The Characteristics, Long-Term Outcomes, Risk Factors, and Antithrombotic Therapy in Chinese Patients With Atrial Fibrillation and Bioprosthetic Valves - Ren, Jiameng; Yang, Yanmin; Zhu, Jun; Wu, Shuang; Wang, Juan; Zhang, Han; Shao, Xinghui (Frontiers in Cardiovascular Medicine, 2021)
Introduction: There were little data about the clinical profiles and long-term outcomes in Chinese patients with atrial fibrillation (AF) and bioprosthetic valves. Methods: The retrospective study enrolled 903 patients with bioprosthetic valve replacement at our hospital and discharged with a diagnosis of AF from January 2010 to December 2018. Results: The median age was 65.6(61.9-69.1) years old, and 548(60.7%) patients were women. During a follow-up period of 3.84(2.64-5.51) years, 68(1.8 per 100 person-years) patients died, 81(2.1 per 100 person-years) patients developed thromboembolism, 23(0.6 per 100 person-years) patients experienced major bleeding. The CHA2DS2 -VASc score, as a categorical variable (low, moderate or high risk), predicted the risk of thromboembolism with the C-statistic of 0.6(95%CI: 0.511-0.689, p=0.046). The incidence of CHA2DS2-VASc score increment was 11.6 per 100 person-years, and the annual reclassification rate of stroke risk (from a low- or moderate group to a higher group) was 12.7%. The current proportion of oral anticoagulants was 52.3%, 59% and 63.2%, respectively in the low, moderate and high stroke risk groups. Age (OR:1.04,95%CI:1.01-1.06,p=0.01), left atrial size(OR:1.05,95%CI:1.03-1.08,p<0.001) and rheumatic heart disease(OR:1.49,95%CI:1.05-2.10,p=0.025) were positively associated with the use of oral anticoagulants. The history of chronic kidney disease (OR:0.20,95%CI:0.05-0.76,p=0.018), prior surgical ablation(OR:0.33,95%CI:0.24-0.47,p<0.001) and antiplatelet agent use(OR:0.08,95%CI:0.05-0.13,p<0.001) were inversely related to the use of oral anticoagulants. Higher admission estimated glomerular filtration rate(HR:0.515,95%CI:0.311-0.853,p=0.01), left ventricular ejection fraction(HR:0.961,95%CI:0.931-0.992,p=0.014), concomitant surgical ablation(HR:0.348,95%CI:0.171-0.711,p=0.004) or rheumatic heart disease history(HR:0.515,95%CI:0.311-0.853,p=0.01) were associated with a lower risk of death. Surgical ablation(HR:0.263,95%CI:0.133-0.519,p<0.001) and oral anticoagulants(HR:0.587,95%CI:0.375-0.918,p=0.019) were related to a lower risk of thromboembolism. Conclusion: Chinese patients with AF and bioprosthetic valve(s) were relatively young and had a high prevalence of rheumatic heart disease with few comorbidities. The percentage of mitral bioprosthetic valve replacement was high; The proportion of concomitant surgical ablation or surgical left atrial appendage occlusion or exclusion was relatively low. The thromboembolic events were the major long-term adverse events. The anticoagulation therapy was underused in patients at moderate or high stroke risk. The CHA2DS2-VASc score was verified to be used for predicting stroke risk in this population. The stroke risk dynamically changed, it needed to be re-estimated once the risk factor changed.